2018
DOI: 10.1016/j.jvs.2017.05.104
|View full text |Cite
|
Sign up to set email alerts
|

External validation of a 5-year survival prediction model after elective abdominal aortic aneurysm repair

Abstract: Objective The benefit of prophylactic repair of abdominal aortic aneurysms (AAAs) is based on the risk of rupture exceeding the risk of death from other comorbidities. The purpose of this study was to validate a 5-year survival prediction model for patients undergoing elective repair of asymptomatic AAA <6.5 cm to assist in optimal selection of patients. Methods All patients undergoing elective repair for asymptomatic AAA <6.5 cm (open or endovascular) from 2002 to 2011 were identified from a single institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…[36][37][38][39] The 5-year survival after EVAR ranges from 57%-75%. [40][41][42][43][44] Previous studies have shown that the majority of deaths after EVAR are due to non-surgical causes such as cardiovascular disease and cancer. 40 Because of these factors, it is difficult to accurately compare long term outcomes among study groups.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] The 5-year survival after EVAR ranges from 57%-75%. [40][41][42][43][44] Previous studies have shown that the majority of deaths after EVAR are due to non-surgical causes such as cardiovascular disease and cancer. 40 Because of these factors, it is difficult to accurately compare long term outcomes among study groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some trials have found statin therapy to be independently associated with better long-term survival of aortic aneurysms. [ 22 23 24 ] Possibly owing to reasons as follows: The pleiotropic effects of statins, which influence endothelial function, inflammatory response, thrombus formation, and plaque stability, could affect postoperative and long-term outcomes. [ 25 26 ] The other effect is thought to be related to downregulation of metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
“…The reported calibration slope of the model was 0.84 and the cstatistic was 0.66. 35 All these long-term prediction models have inherited limitations and require further validation and testing in clinical decision making. A summary of the available AAA decision aids is shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%